"We are not garbage!" the homeless movement in Tokyo, 1994-2002 - Hasegawa, Miki (East Asia (New York, N.Y), 2006)
Offers a full history of a homeless movement in Tokyo that lasted nearly a decade. This book shows how homeless people and their external supporters in the city combined their scarce resources to generate and sustain the movement. It also addresses the origins of increased homelessness and development of homelessness policy in the country.